Optimasi Perancangan Sistem Kontrol Mesin CNC Pengebor PCB berbasis Ant Colony Optimization - Hidayatul Nurohmah; Elfizar Novrianto; Machrus Ali (Universitas Darul Ulum, 2023)
A Print Circuit Board (PCB) is a micro (small) sized board that contains various electronic components that are used in an automatic circuit. PCB drilling is usually done manually with human power, which takes a lot of time when there are more and more holes in the PCB. And precision is required when the drill bit touches the PCB board which creates frictional forces and can cause drilling errors. This research uses data collection after carrying out several simulation methods using Matlab 13a. With optimal division methods including without control, Conventional PID, auto PID and PID - ACO. The aim of this research is to determine the advantages of the Ant Colony Optimization (ACO) method in controlling Computer Numerical Control (CNC) machines. The simulation results show that the best optimization method is produced by the PID - Ant Colony Optimization method which produces overshoot: 0.1199, undershoot: 0.0544, and settling time at 2.532 seconds which is the smallest value, while the design without control never reaches stable steady with the largest undershot. : 0.523. so PID - Ant Colony Optimization was chosen as the best method and is suitable for use in controlling PCB Drilling CNC Machines. By applying the PID - Ant Colony Optimization method to the CNC PCB Drilling Machine, it will be able to produce more precise drilling results